EP311 A single centre retrospective review of all patients treated for cervical cancer with high dose rate brachytherapy at nottingham university hospital NHS trust. (1st November 2019) - Hosni, S; Ellis, C; Weber, P; Anand, A
Abstract : Introduction/Background: Brachytherapy following external beam radiotherapy is vital in the treatment of cervical cancer. High dose rate (HDR) brachytherapy was introduced in 2011 at Nottingham University Hospitals (NUH), with the introduction of MR guided HDR brachytherapy in 2017. This is a retrospective review of all patients receiving HDR brachytherapy during this period. Methodology: A database of all patients receiving HDR brachytherapy at NUH identified patients for inclusion. Retrospective review of electronic medical and radiotherapy records enabled data collection and analysis. Results: 81 patients' records were analysed. 78% of cases had squamous cell histology, 19% adenocarcinoma. Mean age was 54 (range 27–88) years. FIGO staging was as follows: Ib1:6, Ib2:1, IIa:6, IIb:38, IIIa:3, IIIb:7, IIIC1:10, IIIC2:2, IVa:8. 27 patients had a PET CT scan as part of staging, of whom 12 (44%) patients had their cancer upstaged. One case of thyroid cancer and one case of inflammatory bowel disease were diagnosed. A total of 11 patients received induction chemotherapy, 5 within the Interlace trial and 6 outside of a clinical trial. 22 (27%) patients had a complete response on MRI scan prior to HDR brachytherapy. The most common limiting factor in achieving brachytherapy equivalent dose in 2 Gy per fraction to the high risk clinical target volume of 80 Gy was bowel tolerance. Median survival has not yet been reached. 57 (70%) patients are still alive. At recurrence, 1 patient out of 6 with local recurrence had operable disease, 1 patient received palliative chemotherapy and the remainder best supportive care. A total of 12 patients received 1st line palliative chemotherapy and 3 patients received second line chemotherapy. Median survival following palliative chemotherapy was 5 months. Conclusion: This single centre retrospective review reports outcomes for patients treated with HDR brachytherapy for cervical cancer at NUH. Disclosure: Nothing to disclose.